Fostering Multiple Intelligences in Elementary Schools: Harnessing Independent Curriculum-Based Learning in Elementary Schools - Farid, Imam; Bulqois, Nabilah; Assidiq, Nur Alim; Megahutami, Sisi; Iskarim, Mochamad (Tadibia Islamika: Journal of Holistic Islamic Education, 2023)
This study investigates multiple intelligence learning strategies within the context of independent curriculum-based learning (ICBL) in elementary schools. The case study qualitative research method was employed at SD Islam Nusantara, involving first-grade and fourth-grade teachers. Interviews and document analysis were utilized as data collection techniques. The gathered data was analyzed using Miles, Huberman, and Saldana's interactive model, encompassing data condensation, data display, and data drawing. The findings of the study reveal that ICBL has the potential to enhance students' multiple intelligences. The ICBL process fosters improvements in linguistic intelligence, mathematical-logical intelligence, and interpersonal intelligence. Additionally, the project aimed at strengthening the profile of Pancasila students (P5) demonstrates positive effects on existential intelligence, musical intelligence, interpersonal intelligence, naturalist intelligence, and visual-spatial intelligence.